STRATEGI KOMUNIKASI PUBLIC RELATION UNTUK MENINGKATKANKONSUMEN DI PRONTO BAR & RESTO MEDAN - Helen Sitorus Vanhurk Sriwati Ningsih Sitorus; Romantho P Situmorang (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2019)
This research is entitled Public Relations Communication Strategy applied by PRONTO Bar & Resto in increasing consumers. Nowadays the nightly entertainment business is one of the businesses that is quite developed in Indonesia, especially Medan. Clubs or bars are now found in almost places in Medan. As time goes by, various Music Clubs or Bars have been offered to attract public interest in general. So we need a strategy so that companies can continue to grow and be able to face competition. The research object is PRONTO Bar & Resto, this company has an advantage compared to other places by raising the concept of Sporty Bar.The research method used in this study is a descriptive research method, with a qualitative approach. Data obtained from the results of direct interviews with the General Manager of Operations and Chief Marketing Communication, it is also supported by some data from documentation and observation.This study aims to describe the public relations communication strategy carried out by PRONTO Bar & Resto in increasing consumers based on the mix marketing and the elements existing in the promotion mix, namely advertising, sales promotion and word of mouth. Advertising activities are carried out by utilizing Facebook, Instagram and as a direct communication medium with the public, so that communication can be done more communicatively. Promotion stage is done by giving discounts for consumer members and several special packages to attract consumers. Then in the "word of mouth" stage, the company makes a community of consumers in the city of Medan.